(untitled) (Philological Studies, 2019)
The text contains analysis of the war prose, namely short stories describing the siege of Sarajevo. In the centre of interest is a narrative strategy that reflects poetics of the first-hand witnessing. According to that, it specifically analyses how narrators testify about the war; who is the one testifying in those stories and what is the role of a narrator in a story. The published article is part of a wider research that analyses war prose from a narratological, empathetic and ethical aspect.